THE SCIENTIFIC AND TECHNOLOGYCAL REVOLUTION AND ITS IMPACTS ON HUMAN LIFE - Hang, Tran Thu (IJRDO - Journal of Social Science and Humanities Research, 2018)
The author of the article introduces general issues of the revolution in science and technology, its typical features and characteritics, process of fomation and development. On that basis, the author analyzes and presents many evidences to show the impacts of the revolution on the society and people today, including, for example, the strong motives to promote human development trend, and the deep and wide impacts on social production and human life. The author aslo points out some challenges to Vietnam and suggests some solutions for Vietnam to take the opportunities  of the revolution and at the same time to minimize its negative impacts.Of these, the two groups of solutions are well noted by the author, including the development of high- quality human resources and state management institutions.